Jonutytė, J., 2011. Changes in the Concept of Tradition - Būgienė, Lina (Respectus Philologicus, 2012)
Jonutytė, Jurga, 2011. Tradicijos sąvokos kaita. Vilnius: Vilniaus universiteto leidykla. 200 p. ISBN 978-9955-634-67-6